Strategi Pemasaran Produk BSI Oto Di Bank Syariah Indonesia Kcp Medan Marelan - Risky Sobari; Atika Atika (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the marketing strategy for BSI OTO products at KCP Medan Marelan, the type of research method used is a qualitative method, and data collection is carried out by observation and interviews, the data taken is in the form of observations and also from interviews. interview with BSI KCP Medan Marelan officers. Based on the results of the research it was found that the obstacles in marketing BSI OTO at KCP Medan Marelan included inactivity on social media, tight competition from other banks and also the lack of public understanding in the financing application process. and efforts to Overcoming the existing obstacles, BSI KCP Medan Marelan innovates products that will be adjusted to the needs and desires of customers and also adds application facilities in the form of mobile banking and also the BSI website which can make it easier for customers to carry out various transactions and also understand the products available at BSI. and for the marketing strategy of BSI OTO bank BSI KCP Medan Marelan implementing promotions and excellent service, promotions are carried out such as: distributing and distributing brochures, conducting outreach and also conducting promotions indirectly through social media and also excellent service by CS for customers.